Strengthening nutrition interventions in antenatal care services had modest impacts on diet diversity, micronutrient intake, and breastfeeding in Uttar Pradesh, India - Nguyen, Phuong Hong; Kachwaha, Shivani; Tran, Lan Mai; Avula, Rasmi; Young, Melissa F.; Menon, Purnima (American Society for Nutrition, 2020)
Interventions to improve maternal nutrition are poorly integrated into antenatal care (ANC) services in India. Alive & Thrive aimed to strengthen delivery of micronutrient supplements and intensify interpersonal counseling and community mobilization implemented through government ANC services. We evaluated the impact of nutrition-intensified ANC (I-ANC) compared to standard ANC (S-ANC) on diet diversity, consumption of iron-folic acid (IFA) and calcium supplements, and early breastfeeding practices.